Sustainable commodity use : its governance, legal framework, and future regulatory instruments - Oehl, Maximilian Eduard, 1988- (Springer, 2022)
"This open access book examines the governance and legal landscape of the global commodity sector. For that purpose, the author conceptualises both global commodity governance (GCG) as well as transnational commodity law (TCL). He defines the key terms of global commodity governance, delineates the underlying legal framework of transnational commodity law, and assesses the effectiveness of transnational commodity law in fostering a functional commodity sector. Sustainable commodity use is based on a comprehensive analysis of over 250 international agreements, standards, and guiding documents. The author distills the main findings into a conceptualisation of transnational commodity law and provides the reader with a succinct overview of its normative configurations as well as regulatory gaps. Moreover, he elaborates a taxonomy of international commodity agreements. In addition, an outline of the normative substance of transnational commodity law features in an appendix to the main text. The author concludes by making concrete suggestions on how rules regulating commodity activities de lege ferenda could and should be designed to improve the effectiveness of law regulating transnational commodity activity. In doing so, he demonstrates the application of the sustainable use principle as the overall objective and purpose of transnational commodity law and discusses international commodity agreements as future regulatory instruments."
Keywords: Commodity control.; Foreign trade regulation.; Power resources.; Produits commerciaux -- Réglementation.; Commerce international -- Réglementation.; Ressources énergétiques.; energy resources.; Commodity control; Foreign trade regulation; Electronic book.